Eisenbahnlinien und Oberflächenformen in südrussischen Steppenlandschaften - Hempel, Ludwig (ERDKUNDE, 1956)
Using his knowledge, of the terrain, field sketches, photographs and map analysis, the author was able to piece together, though incompletely, the system of the Volga terraces around Stalingrad. On the various terrace levels and along the Volga itself concave forms occur. These are partly fossil but partly still in a state of pronounced development. By plotting these various erosion features - valleys, balki and ovragi - it was possible to determine along the west bank of the Volga a zone of almost 15 Km. in width where erosion is most pronounced. A similar zone at least 20 Km. wide is known to exist along the river Don. On the basis of these natural conditions an attempt is made to elucidate the connections which exist between the routing of the communication lines, viz. the railways, and the physical nature of the region. From observations and map study it emerged that the dependence of the railway routes on the relief features and their formation is considerable and, in the Don and Volga steppe region, is even characteristic. There, this connexion becomes particularly clear since the landforms which influence the communication routes are being rapidly and extensively formed under semi-arid conditions in the unconsolidated deposits. Not only is railway construction in these steppe areas dependent on the surface features, but it is furthermore threatened by their formation processes. In order to avoid the geomorphologically most active denudation zones, other difficulties or dangers such as dam building or snowdrifts have to be contended with.